Ni Supported on Natural Clays as a Catalyst for the Transformation of Levulinic Acid into γ-Valerolactone without the Addition of Molecular Hydrogen - Adrián García; Rut Sanchis; Francisco J. Llopis; Isabel Vázquez; María Pilar Pico; María Luisa López; Inmaculada Álvarez-Serrano; Benjamín Solsona (Energies, 2020)
γ-Valerolactone (GVL) is a valuable chemical that can be used as a clean additive for automotive fuels. This compound can be produced from biomass-derived compounds. Levulinic acid (LA) is a compound that can be obtained easily from biomass and it can be transformed into GVL by dehydration and hydrogenation using metallic catalysts. In this work, catalysts of Ni (a non-noble metal) supported on a series of natural and low-cost clay-materials have been tested in the transformation of LA into GVL. Catalysts were prepared by a modified wet impregnation method using oxalic acid trying to facilitate a suitable metal dispersion. The supports employed are attapulgite and two sepiolites with different surface areas. Reaction tests have been undertaken using an aqueous medium at moderate reaction temperatures of 120 and 180 °C. Three types of experiments were undertaken: (i) without H2 source, (ii) using formic acid (FA) as hydrogen source and (iii) using Zn in order to transform water in hydrogen through the reaction Zn + H2O → ZnO + H2. The best results have been obtained combining Zn (which plays a double role as a reactant for hydrogen formation and as a catalyst) and Ni/attapulgite. Yields to GVL higher than 98% have been obtained at 180 °C in the best cases. The best catalytic performance has been related to the presence of tiny Ni particles as nickel crystallites larger than 4 nm were not present in the most efficient catalysts.